Wind load factors for dynamically sensitive structures with uncertainties. (15th November 2015) - Kwon, Dae Kun; Kareem, Ahsan; Stansel, Rachel; Ellingwood, Bruce R.
Highlights: The current wind load factor may not be adequate for dynamically sensitive structures. Uncertainties associated with dynamic characteristics of flexible buildings need to be considered. A systematic analysis is performed using Monte Carlo simulations based on ASCE 7 procedure. A database-enabled design (DED) procedure is also utilized to support the analysis of the wind load factor. Alongwind and acrosswind load factors for dynamically sensitive structures are estimated. Abstract: The current recommendations for the load factors on wind load in ASCE Standard 7 are based on an analysis of performance of rigid buildings, which may not be adequate for dynamically sensitive structures. In light of the uncertainties associated with dynamic characteristics of flexible buildings such as natural frequency and damping ratio, the load factors for such buildings may deviate from that in ASCE 7. This study investigates the efficacy of the current wind load factor for dynamically sensitive structures in the presence of uncertainties. A systematic analysis is performed using Monte Carlo simulations. Uncertainties associated with each component of the wind load effects such as the wind speeds, natural frequency and damping ratio of a building are incorporated in the load effects based on both ASCE Standard 7-05 and ASCE Standard 7-10 . In addition, a database-enabled design (DED) procedure is utilized to support the analysis of the wind load factor, especially for the acrosswind case where ASCE 7 does not offer any guidance. In addition, the effects of terrain conditions, amplitude-dependent frequency and damping, and negative aerodynamic damping on the wind load factor are also discussed. Recommendations are made for wind load factors for dynamically sensitive structures both in the alongwind and acrosswind directions and for non-hurricane and hurricane winds.